Recycling class: The contradictions of inclusion in urban sustainability - Anantharaman, Manisha (London The MIT Press, 2023)
In Recycling Class, Manisha Anantharaman examines the ideas, flows, and relationships around unmanaged discards in Bengaluru, India, itself a massive environmental problem of planetary proportions, to help us understand what types of coalitions deliver social justice within sustainability initiatives. Recycling Class links middle-class, sustainable consumption with the environmental labor of the working poor to offer a relational analysis of urban sustainability politics and practice. Through ethnographic, community-based research, Anantharaman shows how diverse social groups adopt, contest, and modify neoliberal sustainability$1 (Bs emphasis on market-based solutions, behavior change, and the aesthetic conflation of (3z(Bclean(3y (Bwith (3z(Bgreens
Keywords: Recycling industry; Urban sustainability, Bengaluru; Environmentalism development